Defensive Functioning in Adults with Binge-Eating Disorder - Carlucci, Samantha (Université d'Ottawa / University of Ottawa, 2022)
Introduction: Defensive functioning may play an important role in the development and treatment of binge-eating disorder (BED). The Defense Mechanism Rating Scale (DMRS) is a widely used observer rating measure of defensive functioning. However, there is little research on defensive functioning and the DMRS in BED. This dissertation includes three studies on defensive functioning in individuals with BED. Study one assessed the validity and reliability of the DMRS when used to rate Adult Attachment Interview (AAI) transcripts, and compared defensive functioning between women with and without BED. Study two compared change in defensive functioning in women with BED who received Group Psychodynamic-Interpersonal Psychotherapy (GPIP) versus those in a waitlist no treatment control condition. Study three assessed the impact of other group therapy members’ defensive functioning on an individual group member’s treatment outcomes (i.e., binge-eating frequency and interpersonal functioning). Thus, the overall goals of this dissertation were to better understand the role of defensive functioning in BED, the degree to which defensive functioning changes due to group therapy, and the impact in the context of the therapy group’s defensive functioning on individual outcomes. Method: Participants with for this study were recruited from three previous investigations. Two clinical trials of group psychotherapy provided data of individuals with BED: (1) a randomized trial (N = 85) in which participants were assigned to GPIP (n = 35) or a waitlist control (n = 50), and (2) an uncontrolled study in which all participants with BED (N = 101) received GPIP. A total of 17 therapy groups were formed across both studies, with each group consisting of five to 11 members. In addition, a third study provided data from two comparison groups without BED: women who were overweight/obese (body mass index [BMI] > 27 kg/m2; n = 47) and women who were normal weight (BMI = 20 to 25 kg/m2; n = 49). Participants with BED completed a battery of questionnaires and the AAI at two time-points (i.e., pre-treatment/pre-waitlist and six months post-treatment/post-waitlist). Participants without BED completed the same battery of questionnaires and the AAI at one time-point and did not receive treatment. All AAI audio recordings were transcribed and used to code defensive functioning. Results: In study one, the DMRS coded from AAI transcripts demonstrated acceptable inter-rater reliability; good convergent validity, as it was significantly correlated with other related constructs (i.e., interpersonal functioning, reflective functioning, and attachment insecurity); and acceptable predictive validity, as women with BED had significantly lower defensive functioning than normal weight women without BED. In study two, those who received GPIP had significantly greater improvements in defensive functioning from pre-treatment to six months post-treatment compared to the waitlist control group. Follow-up analyses revealed that the average number of High Adaptive defenses significantly increased from pre-treatment to six months post-treatment in the GPIP condition, but not in the waitlist control condition; and significantly more participants assigned to the waitlist control condition deteriorated in their defensive functioning from pre-waitlist to six months post-waitlist than those assigned to GPIP. In study three, individual defensive functioning scores at pre-treatment were not significantly associated with either treatment outcome (i.e., binge-eating frequency or interpersonal distress) at six months post-treatment. However, other group members’ mean defensive functioning scores at pre-treatment were significantly associated with individual interpersonal distress, but not binge-eating frequency, at six months post-treatment. Discussion: Overall, this dissertation lends further support to the role of defensive functioning in the maintenance and treatment of BED. Individuals with BED tend to use less adaptive defensive functioning, but this can be improved through GPIP. Further, context of the therapy group in terms of defensive functioning is particularly important for improving treatment outcomes in individuals with BED. These findings should be replicated across more diverse samples and other types of group psychotherapy. Group therapists can help their patients with BED confront their maladaptive defense mechanisms and binge-eating by tackling their interpersonal distress, and placing sufficient emphasis on the group’s composition in terms of defensive functioning.
Keywords: binge-eating disorder; defensive functioning; group psychotherapy